The Euro and the Crisis Perspectives for the Eurozone as a Monetary and Budgetary Union - da Costa Cabral, Nazaré; Gonçalves, José Renato; Cunha Rodrigues, Nuno (Financial and Monetary Policy Studies, 2017)
XXVIII, 366 p. 45 illus., 31 illus. in color.